1996
DOI: 10.1136/sti.72.1.47
|View full text |Cite
|
Sign up to set email alerts
|

Sexual health and use of condoms among local and international sex workers in Sydney.

Abstract: Objectives: To compare indicators of sexual health and predictors of condom use for commercial sex among local and international female sex workers first attending an STD clinic. Setting: A public STD clinic in Sydney, Australia. Subjects: All sex workers first attending between June 1991 and May 1993. Methods: Cross-sectional analysis of demographic, behavioural and morbidity data from proforma medical records. Results: 91 local sex workers and 123 international sex workers (predominantly from Thailand, Malay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 13 publications
2
51
0
Order By: Relevance
“…1,2 High STI and increased HIV infection rates in recent migrant sex workers in Sydney have been addressed by a specific sexual health promotion program. 2 A small study of 17 street sex workers, conducted at the Kirketon Road Centre (KRC) in Kings Cross in 1987, suggested that street sex workers had a high incidence of hepatitis B and more general health problems than 'indoor' sex workers surveyed at the same time. They were also more likely to inject drugs than were brothel sex workers.…”
mentioning
confidence: 99%
“…1,2 High STI and increased HIV infection rates in recent migrant sex workers in Sydney have been addressed by a specific sexual health promotion program. 2 A small study of 17 street sex workers, conducted at the Kirketon Road Centre (KRC) in Kings Cross in 1987, suggested that street sex workers had a high incidence of hepatitis B and more general health problems than 'indoor' sex workers surveyed at the same time. They were also more likely to inject drugs than were brothel sex workers.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18] Some studies have been conducted on Asian FSWs who worked abroad in Western countries, but these were conducted mostly in massage parlours 19 or brothels. 20 There is very little research on the risky sexual behaviors of foreign Asian FSWs who engaged in selling sex in nonbrothel entertainment establishments abroad. Singapore, an island city state in Southeast Asia with a population of 4,987,600 21 has, in recent years, experienced a rapid growth in entertainment establishments such as karaoke lounges, night clubs, discotheques, and bars.…”
Section: Introductionmentioning
confidence: 99%
“…1 Numerous studies have sought to estimate the prevalence of sexually transmitted infections (STI), including HIV, among sex workers. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] However, nearly all of these studies have relied on convenience samples, mostly from STI clinics or non-randomly selected sex work venues. The Los Angeles Women Health Risk Study used a rigorous randomised sampling methodology for its cross sectional analysis of street based sex workers in Los Angeles; however, there was no control group against which to compare HIV and STI prevalence.…”
mentioning
confidence: 99%